The conceptual framework for understanding roles of person factors and listening strategy in listening comprehension - Du, Guohui; Chew, Fong Peng; Hasim, Zuwati (The Social Sciences Empowered, 2020)
English listening as an important part of language learning is challenging for most L2/EFL learners. Although many researches have demonstrated that some factors influenced listening success, few researches provided empirical evidence for two or more factors concertedly contributing to effective listening comprehension based on some listening comprehension theories. This study explores how person factors (L2 vocabulary, metacognitive knowledge and self-efficacy) interact, predict listening success directly, and, through strategy, are used indirectly in the listening process. In the present study, the participants are 400 English major students at a college in Anyang, China. Data will be collected through survey questionnaires, aural vocabulary test, and listening level test. Data analysis will be done by SPSS and SEM (structural equation modelling) to figure out their contribution to listening success in the future.